2020
DOI: 10.1080/11356405.2020.1819119
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and interculture: what are teachers doing? (Bilingüismo e intercultura: ¿qué están haciendo los docentes?)

Abstract: One of the main aims of Content and Language Integrated Learning (CLIL) is to develop intercultural awareness and understanding among students. The objective of this study is to analyse whether CLIL primary education teachers implement the intercultural axis of CLIL in the strategies and resources they plan and use in their daily lessons, and which factors may influence this. An open-question questionnaire was used to carry out an in-depth analysis of the opinions of 59 CLIL primary education teachers working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…For example, related studies show that CLIL students are more willing to interact with foreign speakers than their non-CLIL peers, and that their cross-cultural awareness has been reinforced (Roiha & Sommier, 2018;Yang, 2021). However, teachers express difficulties in promoting ICC in CLIL courses, especially when students have grammatical and lexical problems, as they struggle to present both cultural knowledge and linguistic forms to students at the same time (Méndez, 2013;Pérez-Gracia et al, 2020). Additionally, Pawan (2008) has analysed different types of CLIL November 2023 teacher scaffolding and found that cultural scaffolding only accounted for 6% of the studied scaffolds, which offers insufficient evidence for ICC development in CLIL courses.…”
Section: Intercultural Communicative Competence In Clil Coursesmentioning
confidence: 99%
“…For example, related studies show that CLIL students are more willing to interact with foreign speakers than their non-CLIL peers, and that their cross-cultural awareness has been reinforced (Roiha & Sommier, 2018;Yang, 2021). However, teachers express difficulties in promoting ICC in CLIL courses, especially when students have grammatical and lexical problems, as they struggle to present both cultural knowledge and linguistic forms to students at the same time (Méndez, 2013;Pérez-Gracia et al, 2020). Additionally, Pawan (2008) has analysed different types of CLIL November 2023 teacher scaffolding and found that cultural scaffolding only accounted for 6% of the studied scaffolds, which offers insufficient evidence for ICC development in CLIL courses.…”
Section: Intercultural Communicative Competence In Clil Coursesmentioning
confidence: 99%
“…Besides functioning as a directed interaction, the strategy also shows the tactical pattern of a communication process [20]. Moreover, the goals of Intercultural Communication are as follows: (1) understand cultural diversity that influence communication practices, (2) recognized interaction challenges, (3) overcome problems caused by cultural diversity, (4) raise verbal communication and nonverbal skills, and (5) empower effective communication [21].…”
Section: Intercultural Communication Strategymentioning
confidence: 99%